2021
DOI: 10.1111/bcp.15148
|View full text |Cite
|
Sign up to set email alerts
|

Twice neglected? Neglected diseases in neglected populations

Abstract: It is unfortunately true that clinicians lack the necessary evidence to know how to use medications properly in large sections of the population and do not have optimal treatments to use for many neglected tropical diseases (NTDs). NTDs often disproportionately affect neglected populations that are left out of research efforts, such as children and pregnant women. As reliable access to safe, effective preventives and treatments can break the cycle of poverty, illness, and ensuing debility that further perpetua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Tropical vector-borne diseases, such as TL, tend to afflict certain groups in situations of social vulnerability, that is, more susceptible to poverty. 21 COVID-19 unevenly affects poorer men and women, increasing existing inequalities. 22 Maranhão is considered the poorest state in Brazil.…”
Section: Discussionmentioning
confidence: 99%
“…Tropical vector-borne diseases, such as TL, tend to afflict certain groups in situations of social vulnerability, that is, more susceptible to poverty. 21 COVID-19 unevenly affects poorer men and women, increasing existing inequalities. 22 Maranhão is considered the poorest state in Brazil.…”
Section: Discussionmentioning
confidence: 99%
“…Cattle are the primary reservoir of M. bovis and the most significant source of human bTB through consumption of unpasteurised milk, dairy products, raw meat, and inhalation of aerosols (4, 5). While the adverse public health effects of bTB in high-income nations have been mitigated through surveillance, prevention and control (6), bTB remains a global neglected zoonosis that receives insufficient research, policy and public health attention in relation to its health and economic impacts, especially in low- and middle-income settings (7).…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that leishmaniases and social vulnerability are closely related, since it is often accompanied by malnutrition, a weak immune system, lack of resources, precarious housing, and difficulties in getting treatment. , Meanwhile, current antileishmanial drugs are old and highly toxic, and safer presentations are unaffordable to the most severely affected human populations . These aspects demonstrated that the high prevalence of this NTD is still closely associated with neglected communities . Therefore, there is an urgent need for the discovery and development of new efficient pharmacological entities that are more accessible and designed for both the disease and the patient’s needs.…”
mentioning
confidence: 99%